SOSIALISASI BONEKA HORTIKULTURA SEBAGAI PELUANG USAHA DALAM MENINGKATKAN UMKM DESA KAMPUNG TENGAH - Dian Iriani; Afriansyah Afriansyah; Fayyadh Qushayyi Yohan; Barotitta Qiyah; Salmiatil Humam; Fadli Hasri Ansyah; Erlisa Santri; Riska Amelia; Rafifah Azima; Nadia Fitri; Willy Witriani (Universitas Pahlawan Tuanku Tambusai, 2022)
This Horta doll socialization and training activity aims to provide new knowledge and skills to the residents of Kampung Tengah village in making a product that can be used as a business opportunity to increase MSMEs in Kampung Tengah Village. This activity was carried out with a brief presentation of material related to Horta dolls and also training on how to make Horta dolls. This activity was carried out by KKN students in Kampung Tengah village, followed by women from Kampung Tengah village. This Horta doll socialization and training activity received a positive response and appreciation from the residents who participated in the activity. Keywords: Horta doll, MSME